The Cortisol and Androgen Pathways Cross Talk in High Temperature-Induced Masculinization: The 11β-Hydroxysteroid Dehydrogenase as a Key Enzyme - Fernandino, Juan Ignacio (2012)
In many ectotherm species the gonadal fate is modulated by temperature early in life (Temperature-Dependent Sex Determination, TSD) but the transducer mechanism between temperature and gonadal differentiation is still elusive. We have recently shown that cortisol, the glucocorticoid stress-related hormone in vertebrates, is involved in the TSD process of pejerrey, Odontesthes bonariensis. Particularly, all larvae exposed to a male-producing temperature (MPT, 29°C) after hatching showed increased whole-body cortisol and 11-ketotestosterone (11-KT, the main bioactive androgen in fish) levels and developed as males. Moreover, cortisol administration at an intermediate, mixed sex-producing temperature (MixPT, 24°C) caused increases in 11-KT and in the frequency of males, suggesting a relation between this glucocorticoid and androgens during the masculinization process. In order to clarify the link between stress and masculinization, the expression of hsd11b2, glucocorticoid receptors gr1 and gr2, and androgen receptors ar1 and ar2 was analyzed by RT-qPCR and in situ hybridization in larvae reared at MPT, MixPT, and FPT (female-producing temperature, 17°C) during the sex determination period. We also analyzed the effects of cortisol treatment in larvae reared at MixPT and in adult testicular explants incubated in vitro. MPT and cortisol treatment produced significant increases in hsd11b2 mRNA expression. Also, gonadal explants incubated in the presence of cortisol showed increases of 11-KT levels in the medium. Taken together these results suggest that cortisol promotes 11-KT production during high temperature-induced masculinization by modulation of hsd11b2 expression and thus drives the morphogenesis of the testes.